2022
DOI: 10.3389/fpsyg.2022.855089
|View full text |Cite
|
Sign up to set email alerts
|

Visual Attention, Behavioral Intention, and Choice Behavior Among Older Consumers Toward Sports Marketing Images: An Eye-Tracking Study

Abstract: Mental health benefits (i.e., relaxing and relieving pressure) can influence consumers’ consumption decisions. However, there is still no clear understanding of the impact of mental health benefits on visual attention, behavioral intention, and choice behavior. Study 1 was thus aimed at exploring the visual attention and behavioral intention of older consumers with respect to exercise consumption. A sample of 186 older consumers was investigated. An eye-tracking analysis was used to evaluate the visual attenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…Tourism print advertisement serves as a promotional message that is transmitted to the cognitive and affective systems through visual processing, thus affecting destination selection and visit intention of tourists ( Simola et al, 2013 ; John and De'Villiers, 2020 ). A study by Wang et al (2022) using an eye-tracking analysis found that marketing advertisements that combined natural movement scenes with health promotion-focused messages were more likely to be noticed and selected by older consumers. Li et al (2022) found that celebrity endorsement of destinations significantly increased tourists’ visual attention to tourism advertisements, positive destination attitudes, and visit intention.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Tourism print advertisement serves as a promotional message that is transmitted to the cognitive and affective systems through visual processing, thus affecting destination selection and visit intention of tourists ( Simola et al, 2013 ; John and De'Villiers, 2020 ). A study by Wang et al (2022) using an eye-tracking analysis found that marketing advertisements that combined natural movement scenes with health promotion-focused messages were more likely to be noticed and selected by older consumers. Li et al (2022) found that celebrity endorsement of destinations significantly increased tourists’ visual attention to tourism advertisements, positive destination attitudes, and visit intention.…”
Section: Literature Reviewmentioning
confidence: 99%